Unlocking Global Opportunities with “TOEFL Training Program” for Islamic Boarding School Students - Yuzar, Ella; Rahman, Fadhlur (Journal of Community Service and Society Empowerment, 2024)
When it comes to obtaining a higher education in a foreign country, particularly within the context of the TOEFL, it is absolutely necessary to have a strong command of the English language. The objective of this community service project is to familiarize students from Dayah Darul Ulum Al Munawwarah, one of the prestigious Islamic Boarding School in Lhokseumawe, with the TOEFL. This community service program is being carried out through Participatory Action Learning System (PALS). Participants' English language skills in TOEFL are improved through the program, which consists of twelve sessions that are led by two different professional tutors. The program was met with enthusiastic attendance, which highlighted the participants' eagerness to improve their proficiency level in preparation for the students’ future education endeavors. In considering the fact that scores on TOEFL serve as an eligibility requirement for admission to universities located in other countries, this collaborative training initiative plays a crucial role in enabling students from Islamic Boarding School to successfully navigate educational opportunities located in other countries.